2016
DOI: 10.1007/s13238-016-0327-9
|View full text |Cite
|
Sign up to set email alerts
|

Omic studies reveal the pathogenic lipid droplet proteins in non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is an epidemic metabolic condition driven by an underlying lipid homeostasis disorder. The lipid droplet (LD), the main organelle involved in neutral lipid storage and hydrolysis, is a potential target for NAFLD therapeutic treatment. In this review, we summarize recent progress elucidating the connections between LD-associated proteins and NAFLD found by genome-wide association studies (GWAS), genomic and proteomic studies. Finally, we discuss a possible mechanism by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 92 publications
2
21
0
Order By: Relevance
“…HSD17B13 was previously reported to be localized to the LDs in mouse (8) and human (9) hepatocytes. A role of LD-associated proteins in the formation and expansion of LDs as well as in NAFLD progression has been reported in multiple studies (38)(39)(40)(41). Consistent with these observations, we observed increased expression of PLIN2, one of the LD proteins, in hepatic tissues of HSD17B13KO mice.…”
Section: Discussionsupporting
confidence: 92%
“…HSD17B13 was previously reported to be localized to the LDs in mouse (8) and human (9) hepatocytes. A role of LD-associated proteins in the formation and expansion of LDs as well as in NAFLD progression has been reported in multiple studies (38)(39)(40)(41). Consistent with these observations, we observed increased expression of PLIN2, one of the LD proteins, in hepatic tissues of HSD17B13KO mice.…”
Section: Discussionsupporting
confidence: 92%
“…The findings that neutral lipids occupy approximately 5-16% of bovine luteal tissue area is in agreement with other studies examining LD to luteal cell area or volume (27,28,43). In contrast, other tissues rarely contain the same amount of neutral lipids, except during pathological situations (8)(9)(10)(11). Likely, the area occupied by LDs in steroidogenic cells is even greater since luteal endothelial cells account for nearly 50% of luteal tissue (44) but rarely contain LDs (45).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to candidate-gene studies, GWAS are particularly useful for the identification of novel genes associated with diseases that otherwise would have not been considered as candidates due to a limited knowledge of their function. To date, there is compelling evidence of the association of variants in the Patatin-like phospholipase domain containing 3 (PNPLA3) and transmembrane 6 superfamily member 2 (TM6SF2) genes, which are both involved in liver fat retention through lipid droplet remodelling and very-low density lipoprotein (VLDL) secretion, and NAFLD susceptibility and progression to NASH [ 119 , 120 , 121 , 122 , 123 ]. On the other hand, environmental factors and their impact on pathways involved in the pathogenesis of disease can be assessed by other omics analysis.…”
Section: Application Of Omics Technologies In Liver Diseasesmentioning
confidence: 99%
“…While transcriptomics allows the identification of alterations in gene expression, proteomics can be used to monitor changes in protein expression and post-translational modifications at different stages of disease progression. Proteomic studies of NAFLD have revealed 34 candidate biomarkers in liver and serum [ 119 , 122 , 126 ]. Gene or protein expression changes do not always correspond to phenotypic alterations because they operate on a markedly different time scales.…”
Section: Application Of Omics Technologies In Liver Diseasesmentioning
confidence: 99%